PERBEDAAN DAN PERSAMAAN FILSAFAT DENGAN PEMIKIRAN PENDIDIKAN ISLAM - Suhari Suhari (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
The philosophy of Islamic education is essentially a concept of thinking about education that is based on Islamic teachings regarding the nature of human ability to be fostered, developed and guided to become Muslim humans imbued with Islamic teachings. The similarities are that both function to develop knowledge and prepare a generation to have and play a certain role in society, so actually there are not many issues that distinguish education in general from Islamic education.